Phase transformation temperatures (PPTs) and microstructure of moulded NiTi alloy using a water soluble binder system - Muhammad Hussain Ismail; Bram, Martin; Barbosa, Ana Paula Cysne; Kohl, Manuel; Davies, Hywel A.; Todd, Iain (Universiti Kebangsaan Malaysia, 2013)
In this work, the effects of backbone polymer in the binder system mixed with pre-alloyed NiTi powder, on impurity contents, phase transformation temperatures and microstructures were investigated. A spherical gas-atomised pre-alloyed NiTi powder (50.3 at. %Ni) with a mean particle size of less than 22 μm and powder loading of 69.5 vol. % was used. The binder consisted of a water soluble binder system, mainly polyethylene glycol (PEG), with two different backbone binders, namely polyethylene 520 (PE 520) and poly-methyl- methacrylate (PMMA). The latter was used in the form of a powder and as an emulsion. Green parts were prepared by warm-press the feedstock into a cylindrical shape. The samples were then leached in warm water, thermally debound in Argon and finally, vacuum sintered at 1240°C for 10 h. The experimental results indicate that the oxygen content in the as-sintered condition increased to almost double than that of the powder state (from 0.08 to 0.14 - 0.16 wt. %) and the carbon increased by one third to half (from 0.06 to 0.08 - 0.09 wt. %). This consequently resulted in a shift of the phase transformation temperature to lower values and consequently broadened the reversible austenite to martensite transformation. The uptake of oxygen and carbon during the process led to the formation of the well-known Ti4Ni2Ox and TiC precipitate phases which were evident from grey-scale images of back-scattered SEM.